DESIGN AND IMPLEMENTATION OF IOT-BASED CONTROLLER AND USER INTERFACE FOR AMMONIA MONITORING DEVICE IN FISH POND - Yuliarni, Adelia
The marine and fisheries sector is one of the main sectors in Indonesia. Abundant natural wealth with biodiversity, especially in water areas, supports the progress of the existing fisheries sector. Various types of fisheries sector emerged and developed, including fish farming with pond media. Cultivating fish with pond media has a high profit potential, so many farmers are developing and maximizing this cultivation in various ways to increase the profits that can be obtained. One of the efforts made by farmers is to increase the amount of harvest. Optimizing the amount of harvest can be done by providing intensive feed, managing ponds properly and regularly, and using various chemicals to treat diseases that may occur in fish. The high profit potential that can be obtained from fish ponds is accompanied by a high risk of failure. Various management efforts such as high feeding, excessive use of chemicals, and pond turbidity can cause an increase in ammonia levels in ponds, which will then lead to mass mortality of fish. Fish excretion in the form of faeces and urine, accumulated leftover feed, and the use of drugs containing certain compounds are the causes of increased ammonia levels in ponds. To overcome this, farmers usually estimate the relationship between high temperature and high ammonia levels in ponds by dipping their hands directly into the pond. However, measurement in this way can be said to be inefficient, because ammonia levels cannot be detected by simply dipping the hand, ammonia levels can exceed the threshold without the farmer realizing it, so handling cannot be carried out and fish death cannot be avoided. Ammonia monitoring device can help fish farmers monitor ammonia level in fish ponds on a regular basis, and also give immediate alert when ammonia concentrations exceed the safe concentration limit for fish health. This research presents the development of an Internet of Things (IoT) based ammonia level monitoring device control unit and user interface using a Finite State Machine (FSM) behavior model to manage the system. The control unit is able to manage the device subsystems with minimum delay and the user interface is also able to send report periodically and give alert to the user in real time.